1984
DOI: 10.1148/radiology.152.1.6328575
|View full text |Cite
|
Sign up to set email alerts
|

Gallbladder necrosis after transcatheter hepatic arterial embolization: a technique to avoid this complication.

Abstract: We present a technique used to avoid unnecessary embolization of the cystic artery in the treatment of hepatoma by transcatheter arterial embolization. A special long tapering catheter that is flexible and soft enough to be inserted into the distal small branches of the heptic artery is used. Embolic material ( Oxycel , absorbable cellulose) was mixed with Mitocin -C (mitomycin) and contrast material. This mixture will help to avoid reflux.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

1985
1985
2009
2009

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Kuroda explained that reflux of embolic material into the cystic artery is the possible mechanism, and that smaller embolic material may be more likely to induce severe infarction of the gallbladder. Although De Jode et al reported that necrosis of the gallbladder with the likelihood of perforation was the chief danger and recommended cholecystectomy, Kuroda et al [6], Onodera et al [23], and Okamura et al [10] all suggested that these patients can be treated conservatively under close observation. In the literature, no patient experienced perforation of the gallbladder as a result of infarction, but one occurred in our series.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kuroda explained that reflux of embolic material into the cystic artery is the possible mechanism, and that smaller embolic material may be more likely to induce severe infarction of the gallbladder. Although De Jode et al reported that necrosis of the gallbladder with the likelihood of perforation was the chief danger and recommended cholecystectomy, Kuroda et al [6], Onodera et al [23], and Okamura et al [10] all suggested that these patients can be treated conservatively under close observation. In the literature, no patient experienced perforation of the gallbladder as a result of infarction, but one occurred in our series.…”
Section: Discussionmentioning
confidence: 99%
“…Takayasu [17] proposed that such regurgitation was probably due to a sudden change in intraarterial pressure as a result of rapid injection and to bouncing back. Kuroda et al [6] and Onodera et al [23] emphasized that embolus injection should be as slow as possible to avoid reflux. A technique using balloon-tipped catheters has been reported suCcessfully in preventing the reflux during TAE [25]; but failure still occurred in our series in spite of the use of this technique due to too many collaterals in repeated embolization cases.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports state that complete or incomplete occlusion of the cystic artery following TAE has caused se· vere necrosis of the gallbladder. 5 -s There has been no report, however, of gallbladder perforation resulting from TAE ; therefore, this must be a rare complication. Nevertheless, the possibility of such perforation, as in the two cases reported here , must be considered when examining post-TAE patients.…”
Section: Discussionmentioning
confidence: 99%
“…4) with an onionskin appearance in the gallhladder lumen suggesting scaling of the wall, and a hypoechoic mass (fig. 5) suggesting an abscess in the area adjacent to the gallbladder and anterior to the right kidney. Computed tomography, however.…”
mentioning
confidence: 99%
“…Transcatheter arterial embolization was performed according to the method described in a previous report. 7 The embolic material was Oxycel® (absorbable cellulose, Parke-Davis). Oxycel fihers were cut into 0.5-to 1.5-mm pieces and mixed with mitomvcin and a contrast material.…”
Section: Methodsmentioning
confidence: 99%